Wildlife Ungulate Rescue and Emergency Services in the Pisa Area (Tuscany, Italy): Evaluation of a 9-Years Period (2010–2018) - Pacini, Maria Irene; Bonelli, Francesca; Briganti, Angela; Citi, Simonetta; Perrucci, Stefania; Papini, Roberto Amerigo; Sgorbini, Micaela (Frontiers in Veterinary Science, 2020)
Background: We analyzed the ecological and clinical data of wildlife ungulates admitted for emergency care to the Veterinary Teaching Hospital (VTH), Department of Veterinary Medicine, University of Pisa over a 9-year period. Methods: Ecological and clinical data of all the wildlife ungulates admitted to the VTH were recorded. Blood samples were also taken from the animals for haematological and biochemical analysis. An assessment of ecto- and endoparasites (gastrointestinal parasites) was carried out and a diagnostic imaging assessment was performed. Finally, the outcomes were recorded. Results: Data concerning clinical parameters, blood work, parasitological analysis and diagnostic imaging diagnosis were expressed as prevalence. Conclusion: The rescue and emergency treatment were related mostly to traumas caused by car accidents, followed by other causes. The traumatic injuries were mostly severe, characterized by multiple lesions involving hard and soft tissues. This analysis confirms that road accidents are the main cause of wildlife rescue and emergency management. This is probably due to the increased population of ungulates over the years along with the considerable anthropization that characterizes the Pisa area.